How artificial intelligence will effect jobs all around the world - Mohd Kasib Siddiqui (Trends in Computer Science and Information Technology - Peertechz Publications, 2021)
The world is moving towards the era of Artificial Intelligence, most commonly known as automation, at a very great speed. Although, automation may be useful for humans but "How Artificial Intelligence will effect jobs all around the world?" is the real question here. People are already losing their employment because of automation and this is affecting their livelihoods. We have moved from using first generation computers to using and developing fifth generation computers in just 40 years. Previous generations were helpful as they eased our lives but they still had to be operated physically. Artificial Intelligence (AI) was released to remove this need of physical operation and it is already completing its requirement. People are willing to rely on robots and software more and more without realising that this may lead to decrease in employments all around the globe.